A comparison between manual count, flow cytometry and qPCR as a means of determining Babesia rossi parasitaemia in naturally infected dogs - Leisewitz, Andrew L. (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.